SAT0586 Herpes Zoster in The Brazilian Register -Biobadabrasil. (15th July 2016) - Carvalho, H.; Laurindo, I.M.M.; Ranza, R.; Titton, D.; Bertolo, M.; Bianchi, W.; Brenol, C.; Castelar, G.; Castro, G.; Costa, I.; Duarte, A.; Fernandes, V.; et al.
Abstract : Background: Herpes Zoster has been reported with increased frequency in association with rheumatic diseases and biologic therapy. Objectives: To study herpes zoster (HZ) in patients with rheumatic diseases included in the Brazilian Register for monitoring of biologic therapies in rheumatic diseases - BiobadaBrasil, Methods: BiobadaBrasi is a prospective observational cohort study, part of an international initiative (biobadaAmerica) in collaboration with BiobadaSer. Patients with rheumatic diseases are enrolled at the moment of introduction of their first biologic therapy; a comparison cohort of patients with active RA receiving traditional disease-modifying antirheumatic drugs (DMARDs) was recruited in parallel in each center. This register was established in 2009 and is an ongoing study ran by the Brazilian Society of Rheumatology comprising 32 centers (30 public, located at academic centres, 2 private) in almost all states of the country. Data quality is under constant monitoring (online, by phone and "in situ"). In this report all biologic administered to more than a hundred patients were included: abatacept, adalimumab, etanercept, infliximab, rituximab and tocilizumab. Data was expressed as mean (SD); crude incidence rates (IR) were calculated as number of HZ episodes per 1000 patient-years- IR (1000 patient-years). Results: Up to January 2016, 2715 patients were included in the register, 70% female, mean age 51 (14.3) yrs, submitted to 3770 treatments; 1721 patients with diagnosis of RA; $54 with AS and APs=181. 61 HZ episodes were related including only one relapse reported in a 44years-old female patient with AR and in use of rituximab. The crude IR (95% CI) of HZ in the study population (biologic agentes) was 8.3 (1000 patient-years) vs 4.45 (1000 patient-years) in the control population (traditional DMARds), (p=0, 7 95%CI-3, 7–4, 7). Only 6 cases were considered severe by the investigators, two of them were HZ ophthalmicus, one periorbital and all lead to some impairment. These patients were taking different biologic agents (etanercept, adalimumab, infliximab – 2 patients) and one was using traditional DMARDS. Treatment with steroids (HR 1.99; 95%CI 1.092–3.6) was the only factor associated with zoster development. There was no difference in age, sex, specific disease or biologic agent associated with HZ episodes. Conclusions: In our database, the risk of HZ was significantly increased in association with corticosteroid treatment but neither with biologic agents nor with inflammatory rheumatic diseases. Acknowledgement: for monitor P Cabral, for contribution to the BiobadaBrasil registry, L.Barbosa, W.Chahade, A.Hayata, A.Kakehasi, M.Pinheiro, A.Ranzolin, M.Scheinberg, F.Sztajnbok, I.Silveira Disclosure of Interest: None declared